(3fRgI GdSGeY aj GdYed HGdQHY GdLGeYs - (3YdGA GdOjf CHi GdMSf Ydj Hf EHQGgjes; (3GHf GdTGWQ , Ydj Hf EHQGgje Hf eMeO GdCfUGQj GdehbJ, YdGA GdOjf CHh GdMSf,J (B777 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3GdebOeg ai QShe gPG GdQHY GdbWH gh GdHNT GdPi ajg GdNjW hjSei GdeQcR s
(3BNQgG (B:s
(3Ef cGf eWGdYgG CcKQ aGQJaGYg ZQjHkG aGYde Pdc hdfLYd gPG GdcdGe BNQ GdQSGdg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B251 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B8s
Keywords: (3Gdadcs